Children as Domestic Workers: Legal Challenges - Ahlawat , Sonika (Trinity Law Review, 2024)
The involvement of children in the domestic work which is categorised under  unorganised sector of labour is an extensive and growing worldwide phenomenon.  Specifically in the case of India, the preamble of the Constitution embarks on  the word ‘We’ and imparts equal rights to all the citizens of the country without  any discrimination. Some special provisions were cautiously incorporated in the  Constitution for protection of the children like, Articles 21A (Right to Education),  23 (Protection against trafficking & other forms of forced labour), 24 (prohibition  of employment of children in factories etc.), 39(e) (Protection from abuse) etc. In this unorganised sector almost 40 per cent work is performed by the children  who mostly migrate from rural to urban areas. To meet the basic necessities of life,  these children are forced to work in private households under severe conditions  such as long and unregulated working hours, employment subject to employer’s  mercy, and high level of insecurity. They remain vulnerable as they work in  unorganised sector that is constituted mainly by the marginalised people, living  mostly in slums in shabby conditions, and remain subject to exploitation in the  absence of specific legislative frameworks to regulate their working conditions.  These working conditions impinge on the fundamental rights of the children  guaranteed by the Constitution of India. Recently, some measures have been initiated to bring this sector in the legislative  ambit, under the Code on Social Security which defines the term “wage worker”,  including the domestic workers. A reality check indicates there is not a single  provision in this Act to assure social security to the children working as domestic  help; instead, it excludes them from the various provisions of labour laws. This paper attempts to outline the legislative provisions at national as well as  international level for the protection of children, challenges faced by the children  working as domestic workers, role of judiciary to curb the problem and outline the  policy postures required to adopt an inclusive approach to afford social justice and  facilitate their economic and social inclusion as per the spirit of the Constitution.
Keywords: Children; Constitution; domestic help; legal rights; legislative framework